Euroregionalna współpraca miast podzielonych na zachodnim pograniczu Polski - znaczenie dla rozwoju turystyki - MARIANNA GRETA; JACEK OTTO (Ekonomiczne Problemy Turystyki, 2018)
Functioning of Polish euroregions for more than 20 years has resulted in differentiation and con¬tinuous enrichment of forms of cooperation within them. This is particularly true in the western borderland of Poland, because we have here a partner of the euroregional initiator of this form of cooperation, ie the German side. On this border it took place among others euroregional speciali¬zation in the form of the so-called: divided cities (Gubin-Guben, Zgorzelec-Gorlitz, Słubice- Frankfurt on the Oder). Among the many directions of cooperation, the main are activities conducive to the development of tourism and recreation, which contribute to the activation of peripheral border regions and the raising of development indicators.